A terceira idade na educação de jovens e adultos: expectativas e motivações - Isamara Grazielle Martins Coura (2007)
The research quested after comprehending the reasons which take literate Senior citizens and who, probably, did not have as aim the integration, permanence or reintegration in the labor market, to go back to study. Besides this, it was also intended to identify which expectations these subjects have in relation to education and to what extent they have been fulfilled. It is about an investigation of qualitative character that, in order to be accomplished, had as relevant criteria the age choice regarding the researched subjects - they had to be more than 60 years old and to be in different school grades in the Education of Youths and Adults (EJA Educação de Jovens e Adultos). So, the research was conducted with seven students, three men and four women, in the age between 60 and 81 years old, by the time they were interviewed. Among these, two had already concluded the fundamental education and the others attended different grades of the course in the Fundamental Teaching Project of the Second Segment (PROEF II) of UFMG (Universidade Federal de Minas Gerais Federal University of Minas Gerais). Based on these students report, we could know their school difficulties until they arrived in EJA. Thus, it was possible, through their life stories, their difficulties faced without a well structured school knowledge, the highlight they gave to the activities, moments and spaces considered as their favorite ones, in their education process, to perceive what school means to these subjects. It was also possible to point out some contributions, brought by the act of education, for the improvement of life quality of the people who, as the interviewed ones, are in the same age.